2007
DOI: 10.1007/s10606-007-9044-5
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Negotiating Artifacts: Unbinding the Routine of Boundary Objects and Embracing Chaos in Collaborative Work

Abstract: Empirical studies of material artifacts in practice continue to be a rich source of theoretical concepts for CSCW. This paper explores the foundational concept of boundary objects and questions the conception that all objects that move between communities of practice are boundary objects. This research presents the results of a year-long ethnographic study of collaborative work, specifically the multidisciplinary collaborative design of a museum exhibition. I suggest that artifacts can serve to establish and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
278
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(290 citation statements)
references
References 22 publications
4
278
0
8
Order By: Relevance
“…Other times, the text proves too abstract and vague, masking its value and making it unattractive for musicians to read. These texts reflect the observation of Lee (2007) that ''unstandardized artifacts that are partial, incomplete, or are intermediary representations are ubiquitous in collaborative work. '' When Star and Griesemer (1989) and Lee (2007) talk of boundary (negotiating) objects, they speak of material artifacts.…”
Section: Representing the Aesthetics Of Receptionmentioning
confidence: 55%
See 1 more Smart Citation
“…Other times, the text proves too abstract and vague, masking its value and making it unattractive for musicians to read. These texts reflect the observation of Lee (2007) that ''unstandardized artifacts that are partial, incomplete, or are intermediary representations are ubiquitous in collaborative work. '' When Star and Griesemer (1989) and Lee (2007) talk of boundary (negotiating) objects, they speak of material artifacts.…”
Section: Representing the Aesthetics Of Receptionmentioning
confidence: 55%
“…These texts reflect the observation of Lee (2007) that ''unstandardized artifacts that are partial, incomplete, or are intermediary representations are ubiquitous in collaborative work. '' When Star and Griesemer (1989) and Lee (2007) talk of boundary (negotiating) objects, they speak of material artifacts. However, instead of trying to decipher when a tune becomes ''materialized'' (e.g., when it is played), I believe it more constructive to emphasize the creative process involved in representation via the lens of reader-reception theory.…”
Section: Representing the Aesthetics Of Receptionmentioning
confidence: 55%
“…On the other hand, the literature on multiparty IT development efforts reveals that there nowadays are parties from numerous organizations and even countries involved, representing different kinds of areas of expertise: not only technology, marketing and business, but also strategy, manufacturing, education, curation, meteorology etc. [5,19,20,21,22]. In this kind of a design team collaboration is a true challenge [e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In multiparty design teams, in which there are experts representing different disciplines, professions, organizations and nationalities cooperating, it has been reported that communicating, collaborating, and arriving at shared understandings are very challenging [5,19,20,21]. However, knowledge sharing and the creation of shared understandings are also postulated as vital for successful multiparty design teams.…”
Section: Usability Specialists As Boundary Spannersmentioning
confidence: 99%
See 1 more Smart Citation